2020
DOI: 10.1111/echo.14901
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of anomalous origin of the right subclavian artery from the right pulmonary artery in a patient with D‐transposition of the great arteries utilizing transthoracic echocardiography

Abstract: Diagnosis of anomalous origin of the right subclavian artery (AORSA) from the right pulmonary artery (RPA) is usually made using CT, MRI, or invasive angiography. We report a patient diagnosed using transthoracic echocardiography (TTE). A newborn girl prenatally known to have d-TGA presented with cyanosis sparing the right hemithorax and arm. Oxygen saturations on the right hand were persistently higher than on the right ear and other extremities. Repeat TTE using a modified echocardiographic imaging plane all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…2 Isolation of the subclavian artery in association with d-TGA is rarer still. Investigators describe several case reports of isolated right subclavian artery from the right pulmonary artery with d-TGA [3][4][5][6][7][8][9] and only two reports of an isolated left brachiocephalic with d-TGA. 10,11 There are two reports of an isolated LSA with d-TGA, by Byrum et al, 12 who described the diagnosis confirmed by cardiac catheterization with angiography, and Siddartha et al, 13 who described a patient with d-TGA who underwent an arterial switch operation on the fourth day of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Isolation of the subclavian artery in association with d-TGA is rarer still. Investigators describe several case reports of isolated right subclavian artery from the right pulmonary artery with d-TGA [3][4][5][6][7][8][9] and only two reports of an isolated left brachiocephalic with d-TGA. 10,11 There are two reports of an isolated LSA with d-TGA, by Byrum et al, 12 who described the diagnosis confirmed by cardiac catheterization with angiography, and Siddartha et al, 13 who described a patient with d-TGA who underwent an arterial switch operation on the fourth day of life.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is most commonly made by cardiac computed tomography, CMR, or invasive angiography. However, it can be made by echocardiography 4 and requires thorough interrogation of the branching pattern of the head and neck vessels. Although arch sidedness and branching are classically defined in the suprasternal axial view with a sweep superiorly, locating the origin of an anomalous subclavian artery requires slow sweeps inferiorly to visualize the main and branch pulmonary arteries, as described by Makadia et al 4 Thus, when arch branching anatomy is unclear from typical suprasternal sweeps, further evaluation of each head and neck vessel's origin is necessary to define the anatomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations